Roles of transmembrane protein 135 in mitochondrial and peroxisomal functions - implications for age-related retinal disease - Landowski, Michael; Gogoi, Purnima; Ikeda, Sakae; Ikeda, Akihiro (Frontiers in Ophthalmology, 2024)
Aging is the most significant risk factor for age-related diseases in general, which is true for age-related diseases in the eye including age-related macular degeneration (AMD). Therefore, in order to identify potential therapeutic targets for these diseases, it is crucial to understand the normal aging process and how its mis-regulation could cause age-related diseases at the molecular level. Recently, abnormal lipid metabolism has emerged as one major aspect of age-related symptoms in the retina. Animal models provide excellent means to identify and study factors that regulate lipid metabolism in relation to age-related symptoms. Central to this review is the role of transmembrane protein 135 (TMEM135) in the retina. TMEM135 was identified through the characterization of a mutant mouse strain exhibiting accelerated retinal aging and positional cloning of the responsible mutation within the gene, indicating the crucial role of TMEM135 in regulating the normal aging process in the retina. Over the past decade, the molecular functions of TMEM135 have been explored in various models and tissues, providing insights into the regulation of metabolism, particularly lipid metabolism, through its action in multiple organelles. Studies indicated that TMEM135 is a significant regulator of peroxisomes, mitochondria, and their interaction. Here, we provide an overview of the molecular functions of TMEM135 which is crucial for regulating mitochondria, peroxisomes, and lipids. The review also discusses the age-dependent phenotypes in mice with TMEM135 perturbations, emphasizing the importance of a balanced TMEM135 function for the health of the retina and other tissues including the heart, liver, and adipose tissue. Finally, we explore the potential roles of TMEM135 in human age-related retinal diseases, connecting its functions to the pathobiology of AMD.